GOLIBRAS: uma ferramenta para divulgação dos sinais da UFPA - LIBONATI, Ana Carolina Delgado Quaresma (Universidade Federal do Pará, 2020)
This work is about the development of the Online Glossary of Brazilian Sign Language (GOLIBRAS), a glossary of Libras aimed at the deaf community of the Federal University of Pará (UFPA), covering, in its prototypical phase, 29 signs referring to places of the university. We sought to answer the following question: how to provide greater access to Libras signs created within the context of UFPA? The product development was based on an applied research, with a qualitative approach, divided into two phases: one focused on theoretical research, with a bibliographic review; the other one focused on the development of the product and it was divided into three subphases: cataloging of signs, elaboration of the website (its characteristics and functionalities) and evaluation. The bibliographic research was initially focused on linguistic studies of Libras and its speakers, highlighting the notion of deaf community, the signal language parameters (the phonetic aspect of these languages), the classifiers and the SignWriting model. After that, accessibility and its importance were investigated, as well as the accessibility initiatives within the scope of UFPA, highlighting the role of the Accessibility Coordination (CoAcess), responsible for the creation and validation of the signals included in the initial version of GOLIBRAS. In the second part of the research, the development of the product, a cataloging sheet was first developed for the cataloging of signs of UFPA’s places and facilitating their insertion into the product. After that, it was possible to develop the site itself, including all the mentioned signs, besides its definition, example of use and information regarding the parameters used in its execution and its writing in SignWriting. Finally, the product was validated by six individuals, all members of the deaf communities of UFPA and the Federal Rural University of Amazonia (UFRA). The product was considered validated, given the positive reception by the evaluators, but it was clear that some modifications would be necessary. Thus, it was concluded that GOLIBRAS has the capacity to achieve the proposed objective and is a tool that has the potential to assist both in the issue of accessibility in UFPA and in the teaching and learning processes that includes deaf students, deaf and listeners professors and sign language intepreters.